Post menopause and Osteoporosis - Unfolding the link - Sahithi, Dathar; Reddy, Sudhakara; Rajesh, N.; Priyadarshini, Sheela; Krishnan, Meenakshi; Upendra, Gurugubelli (International Journal of Medicine, 2015)
Background: Osteoporosis is one of the most systemic diseases prevalent among the postmenopausal women attributing to the increased risk of occurrence of fractures. Hence, early detection of this disease is of utmost importance which can be determined by concentration of calcium in saliva and radiographically by quantitative radiomorphometric indices like panoramic mandibular Index (PMI).Objectives: The purpose of this study is to evaluate and compare the salivary calcium levels and PMI in order to identify the risk group of osteoporosis in postmenopausal women.Methods: A case-control study was carried out among 60 female subjects who were equally categorized into two groups. Salivary calcium levels were calorimetrically assessed by spectrophotometry and PMI index was calculated using Digora software from the Digital Panoramic image obtained for individual patient.Results: The results had shown that salivary calcium among the case group was significantly higher than the control group (p value = 0.001) and PMI values among the case group were significantly lower than the control group (p value = 0.001).With the advancing duration of menopause, the salivary calcium levels were increasing and PMI values were found to be decreasing and both were statistically significant.Conclusion: The results of this study suggest that both salivary calcium and PMI can certainly be used as screening tools to identify the risk of osteoporosis among postmenopausal women.